2010
DOI: 10.1007/s10562-010-0312-5
|View full text |Cite
|
Sign up to set email alerts
|

Passive NOx Reduction with CO Using Pd/TiO2/Al2O3 + WGSR Catalysts Under Simulated Post-Euro IV Diesel Exhaust Conditions

Abstract: This study deals with diesel DeNO x catalysis by physically mixed Pd/TiO 2 /Al 2 O 3 and water-gas-shiftreaction (WGSR) catalysts under CO-rich conditions at a CO/NO x ratio of 16. In the post-Euro IV era, many diesel engines are expected to produce CO-rich exhaust emissions due to the trend toward emission regulation and limitations in related technologies. Under these circumstances, the passive DeNO x strategy utilizing CO as a single reductant can be considered appropriate. The Pd/TiO 2 /Al 2 O 3 catalyst i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Another promotional strategy was developed by Hong et al 101 via physically mixing a conventional SCR catalyst (Pd/ TiO 2 /Al 2 O 3 ) with a water−gas shift reaction (WGSR) catalyst (Cu/ZnO/Al 2 O 3 ). It was found that the SCR activity was remarkably improved at temperatures over 300 °C, and the optimal ratio of Pd/TiO 2 /Al 2 O 3 + Cu/ZnO/Al 2 O 3 was 33:67.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Another promotional strategy was developed by Hong et al 101 via physically mixing a conventional SCR catalyst (Pd/ TiO 2 /Al 2 O 3 ) with a water−gas shift reaction (WGSR) catalyst (Cu/ZnO/Al 2 O 3 ). It was found that the SCR activity was remarkably improved at temperatures over 300 °C, and the optimal ratio of Pd/TiO 2 /Al 2 O 3 + Cu/ZnO/Al 2 O 3 was 33:67.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…Another promotional strategy was developed by Hong et al . via physically mixing a conventional SCR catalyst (Pd/TiO 2 /Al 2 O 3 ) with a water–gas shift reaction (WGSR) catalyst (Cu/ZnO/Al 2 O 3 ).…”
Section: Catalyst Components and Their Roles In H2-scr Catalystsmentioning
confidence: 99%
“…In addition, these emissions play a critical role in global warming and greenhouse effects. NOx also causes acid rain and destruction of the ozone layer [6][7][8]. Therefore, emission control is tremendously momentous in diesel engines [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Significant attention has been given to the development of selective catalytic reduction (SCR) of NO x using H 2 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], CO [19][20][21], or a mixture of H 2 /CO [22][23][24][25][26][27][28][29][30][31][32][33] as reductant. Catalysts using H 2 and/or CO have the advantage of lowtemperature DeNO x activity, and the reductants could be produced using an on-board fuel reformer, thus eliminating the need of carrying any additional reductant.…”
Section: Introductionmentioning
confidence: 99%